Analysis of learning the front crawl stroke by use or non-use of instructional flotation devices - Scurati, R.; Roione, G. C.; Michielon, G.; Invernizzi, P. L. (Biomechanics and Medicine in Swimming X, 2006)
A current methodological problem for Italian swimming teachers is the suitability of the instructional flotation devices as a useful tool for the learning process of swimming. In literature, there are several studies reporting contrasting results in the use of these aids. The present study analyses the results of the front crawl stroke learning process in Italian children aged 8-9 years after a 10 lessons program developed by the use or non-use of instructional flotation devices. Both a qualitative (by MERS-F scale) and a quantitative (armstroke cycles, breathings, stroke rate, stroke length, efficiency index) analyses were performed. No significant differences between the two methods were found.